A Production system study report on General Motors Pilipinas, Inc. Transmission Plant - Yenko, Anthony; Gadong, Marjorie; Ludovice, Lyna.; Villadiego, Rafael (Diliman, Quezon City College of Engineering, 1985)
The first part of the report dwells on the leghty documentation of the production system of General Motors.Although the documentation has touched on almost all aspects of the production system,its main focus is the production planning and control of the company.After in-depth analysis,the group is able to make the following recommendations:1.Continue the uses of the present method of sales forecasting although caution should be exercised in dealing with the demand figures given by the buyers themselved.2.Consider the use of programming techniques in production planning as these techniques minimize the inccurence of opportunity costs resulting from the non-optimal scheduling of production.3.Consider seriously the application of programming techniques in the plannin of materials inventory,as present system results in excessive inventory of some purchased components.4.Continue with the present rigid standards of quality control, more specifically with 100% inspection.
Submitted in partial fulfillment of the course requirements in IE 151 : Production Systems
Keywords: General Motors Pilipas; Motors industry; Production engineering